Early Pleistocene fauna of the Olteţ River Valley of Romania: Biochronological and biogeographic implications. (10th July 2020) - Terhune, Claire E.; Curran, Sabrina; Croitor, Roman; Drăgușin, Virgil; Gaudin, Timothy; Petculescu, Alexandru; Robinson, Chris; Robu, Marius; Werdelin, Lars
Abstract: The Early Pleistocene of Eurasia is marked by significant climatic, environmental, and faunal shifts and is the time during which Homo first appears in the Eurasian fossil record. To better characterize the environments that were available to these hominins, accurate data regarding the faunal composition of eastern European sites are necessary, as this is the region through which Homo is hypothesized to have dispersed into Europe. Here we present updated and revised taxonomy and biochronology for sites in the Olteţ River Valley (ORV) of central Romania. The site of Grăunceanu is one of the most fossiliferous deposits from this time. Excavations and descriptions of the ORV sites took place during the 1960–1980s, but since that time many taxonomic revisions have been published. Here, we present a reassessment and update of the fauna from the ORV sites. We report several new taxa (e.g., Pachystruthio, Smutsia ) and expand the known biogeographic range for other taxa (e.g., Puma pardoides ). Our biochronological assessment of this updated taxonomy is consistent with previous reports, though with some refinement. We suggest Grăunceanu is Late Villafranchian ( 2.2–1.9 Ma) and compositionally similar to the sites of Saint-Vallier (France) and Vatera (Greece). Similarly, the La Pietriş assemblage was likely deposited >1.7 Ma. The younger site of Fântâna lui Mitilan was deposited after 1.8 Ma, and perhaps as recently as 1.1 Ma. Thus, the ORV faunal assemblages provide an excellent record of nearly the entire span of the Late Villafranchian for both central Romania and eastern Europe.